Ameliorative effects of type-A procyanidins polyphenols from cinnamon bark in compound 48/80-induced mast cell degranulation - Kandhare, Amit D. (Anat Cell Biol, 2017)
Allergic diseases are a significant health concern in developing countries. Type-A procyanidin polyphenols from cinnamon (Cinnamomum zeylanicum Blume) bark (TAPP-CZ) possesses antiasthmatic and antiallergic potential. The present study was aimed at the possible anti-allergic mechanism of TAPP-CZ against the compound 48/80 (C48/80)–induced mast cell degranulation in isolated rat peritoneal mast cells (RPMCs). TAPP-CZ (1, 3, 10, and 30 µg/ml) was incubated for 3 hours with isolated, purified RPMCs. The C48/80 (1 µg/ml) was used to induce mast cell degranulation. The mast cell viability was assessed using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay whereas histamine, β-hexosaminidase (β-HEX), and interleukin-4 (IL-4) levels were determined in RPMCs. TAPP-CZ (3, 10, and 30 µg/ml) showed significant and dose-dependent decrease in a number of degranulated cells and levels of markers (histamine, β-HEX, and IL-4) as compared with C48/80 control. In conclusion, TAPP-CZ stabilizes mast cell and cause inhibition of the allergic markers such as histamine, IL-4, and β-HEX in IgE-mediated manner. The present study supports mast cell stabilization as a possible mechanism of action of TAPP-CZ against immune respiratory disorders such as asthma and allergic rhinitis.